Oceanographic drivers of sablefish recruitment in the California Current. (30th March 2018) - Tolimieri, N.; Haltuch, M. A.; Lee, Q.; Jacox, M. G.; Bograd, S. J.
Abstract: Oceanographic processes and ecological interactions can strongly influence recruitment success in marine fishes. Here, we develop an environmental index of sablefish recruitment with the goal of elucidating recruitment‐environment relationships and informing stock assessment. We start with a conceptual life‐history model for sablefish Anoplopoma fimbria on the US west coast to generate stage‐ and spatio‐temporally‐specific hypotheses regarding the oceanographic and biological variables likely influencing sablefish recruitment. Our model includes seven stages from pre‐spawn female condition through benthic recruitment (age‐0 fish) for the northern portion of the west coast U.S. sablefish stock (40°N–50°N). We then fit linear models and use model comparison to select predictors. We use residuals from the stock‐recruitment relationship in the 2015 sablefish assessment as the dependent variable (thus removing the effect of spawning stock biomass). Predictor variables were drawn primarily from ROMS model outputs for the California Current Ecosystem. We also include indices of prey and predator abundance and freshwater input. Five variables explained 57% of the variation in recruitment not accounted for by the stock‐recruitment relationship in the sablefish assessment. Recruitment deviations were positively correlated with (i) colder conditions during the spawner preconditioning period, (ii) warmer water temperatures during the egg stage, (iii) stronger cross‐shelf transport to near‐shore nursery habitats during the egg stage, (iv) stronger long‐shore transport to the north during the yolk‐sac stage, and (v) cold surface water temperatures during the larval stage. This result suggests that multiple mechanisms likely affect sablefish recruitment at different points in their life history.